Soft tissue sarcomas in 2 zoo-housed Alaskan moose. (July 2022) - Walker, Bridget; Eustace, Ronan; Junge, Randall E.; Hsu, Tu Chun; Watson, Victoria
Soft tissue sarcomas (STSs) are common well-described cutaneous neoplasms in many domestic species. Few cutaneous neoplasms have been reported in cervids, other than papilloma virus–induced benign cutaneous fibromas (BCFs). Two wild-caught Alaskan moose ( Alces alces ), housed at different North American zoos, were both presented with lameness and a mass. The gross appearance of each mass varied greatly; case 1 had a distinct, exophytic, ulcerated mass near the right carpal joint similar in appearance to a BCF, and case 2 had a pronounced swelling over the left hip. Based on histologic evaluation, both masses were diagnosed as STS. The clinical presentation of these masses included rapid growth and associated lameness; however, gross appearance was markedly different. Histopathology revealed characteristics typical of STS in other species, including spindle-shaped cells arranged in streaming sheets with ovoid nuclei. STS should be included as a differential diagnosis for moose with a cutaneous or subcutaneous soft tissue mass or swelling.